Treating drug abusers - Bennett, Gerald, 1951- (Routledge, 1990)
A clear, practical guide to current approaches in the treatment of drug-taking. Taking a psychological perspective, the authors focus on, among other things, relapse and its prevention, family therapy, and transmission of HIV virus.